RASIO LIKUIDITAS, SOLVABILITAS, DAN AKTIVITAS TERHADAP KINERJA KEUANGAN PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2019-2022 - Isnaini, Fikri Ardan; Sugeng, Sugeng; Astuti, Puji (Universitas Nusantara PGRI Kediri, 2023)
The purpose of this study is to examine the impact of liquidity ratios represented by liquidity ratios, solvency ratios determined by debt to equity ratios, and activity ratios determined by total asset turnover ratios. , to determine financial performance, determined by partial and concurrent asset returns. The samples used in this study were 18 of 31 food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2022 period. Data collection and quantitative techniques use secondary data. Multiple regression analysis was used in this study. The results showed that the results of the current ratio, debt to equity ratio, and total asset turnover ratio affect investment returns if tested at the same time or at the same time. In part, liquidity ratios and asset turnover ratios affect ROA. While the debt-to-equity ratio may not have a significant impact on ROA.